2013
DOI: 10.3855/jidc.2771
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Influenza A(H1N1) in Cote d'Ivoire: health-care providers’ knowledge of influenza and attitudes towards vaccination

Abstract: Introduction: During the 2009 influenza A(H1N1) pandemic (pH1N1), different methods were promoted to reduce the spread of influenza, including respiratory etiquette and vaccination. To identify knowledge gaps about influenza and to plan the vaccination campaign against the pandemic in Côte d'Ivoire, a survey was conducted among health-care providers (HCPs) to assess their knowledge about influenza and their willingness to be vaccinated. Methodology: A cross-sectional survey was performed in the city of Abidjan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(42 reference statements)
1
4
0
1
Order By: Relevance
“…Despite limited vaccine knowledge, most primary caregivers said they would get an influenza vaccine if available for free, although this proportion varied by site. While studies of vaccine acceptability among primary caretakers in the community are limited, willingness to accept influenza vaccine in this study was similar to acceptability observed among healthcare workers in Kenya16 and Cote d'Ivoire17 and higher than acceptability observed among pregnant women in Cote d'Ivoire18 during the 2009 influenza A (H1N1) pandemic. We did not explore how clinician recommendations, which have been shown to influence vaccination attitudes and practices,19 might affect willingness to receive influenza vaccine in this population.…”
Section: Discussionsupporting
confidence: 68%
“…Despite limited vaccine knowledge, most primary caregivers said they would get an influenza vaccine if available for free, although this proportion varied by site. While studies of vaccine acceptability among primary caretakers in the community are limited, willingness to accept influenza vaccine in this study was similar to acceptability observed among healthcare workers in Kenya16 and Cote d'Ivoire17 and higher than acceptability observed among pregnant women in Cote d'Ivoire18 during the 2009 influenza A (H1N1) pandemic. We did not explore how clinician recommendations, which have been shown to influence vaccination attitudes and practices,19 might affect willingness to receive influenza vaccine in this population.…”
Section: Discussionsupporting
confidence: 68%
“…Of all 470 studies, 42 reported affective parameters of risk perception as significant barriers to influenza vaccination, i.e. low worry about the disease (HCP 7/117 [ 39 , 40 , 129 133 ]; Pregnant 3/35 [ 117 , 134 , 135 ]; Elderly 1/62 [ 136 ]; Public 24/191 [ 61 64 , 79 , 102 , 120 , 121 , 137 152 ]) and low anticipated regret in the case of not being vaccinated (HCP 1/117 [ 153 ]; Pregnant 1/35 [ 134 ]; Public 5/191 [ 78 , 154 157 ]). For example, Tucker et al report that pregnant women in a US sample who worried about influenza were approximately 3 times more likely to get the flu vaccine even when adjusting for cognitive risk parameters like probability and susceptibility of the disease [ 135 ].…”
Section: Resultsmentioning
confidence: 99%
“… 7 The vaccine intention of Ivorian HCWs during the AH1N1 influenza pandemic was 80% and the reasons for this decision were fear for the disease or even contracting the disease. 23 Labor pressure (39.8%), negligence (38.8%), vaccine cost (20.9%) were also found to be a barrier to HBV vaccination among HCWs in Pakistan. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 20-21 In Côte d’Ivoire, studies have been conducted on the vaccination status of HCWs, 22 their acceptance of vaccination, and their recommendation to patients during the epidemic period. 23 There has been an absence of research on the relationship between the vaccination status and perceptions of HCWs and their vaccine practices with their patients. This study was conducted to improve the vaccine practices of HCWs.…”
Section: Introductionmentioning
confidence: 99%